A review on the service delivery and administrative services in local governance - Shrestha, Rubina; Bhandari, Bhuwan; Chhetri, Pankaj Kumar (Innovative Research Journal, 2024)
In the field of public administration and public policy, service delivery and administrative services are very closely interrelated. By their nature and function, both have the same or equal way of functioning. The aim of any administrative mechanism is to provide services to the people. In this matter, providing service to the people is a core and practical part of administrative service delivery. The thematic review of published literature is the main way to interpret the data. From this paper, every step of government in every nation is to provide service to meet the demands of the general people, and to provide administrative satisfaction is core. The services provided by the government are impartial, and the people are satisfied with the service delivery by the system. Service delivery and people’s satisfaction are considered administrative service delivery for the sake of good governance. The provision of services is one part, and how these services have been provided is another part that determines the performance of governments in every step. It is expected as well as normative that the administrative services should be provided in an impartial and satisfactory manner.